Enhancing competitiveness through technology transfer and product quality: The mediation and moderation effects of location and asset value - Patient Rambe; Peter Khaola (Journal of Innovation and Entrepreneurship, 2023)
The direct effects of technology transfer and innovation on the productivity and competitiveness of economies and businesses are well established. However, research is yet to establish the explanatory variables and the boundary conditions within which these relationships exist. This study examines the extent to which product quality mediates the relationship between technology transfer and competitiveness of small-scale agricultural businesses (SSABs). Moreover, the study explores the extent to which the geographical location moderates the technology transfer-business competitiveness relationship, including whether asset value moderates the product quality-competitiveness relationship. A cross-sectional survey was conducted on 400 SSAB owners and managers in the Free State and Mashonaland Central Provinces of South Africa and Zimbabwe, respectively. Of the 400 questionnaires distributed, 268 usable questionnaires (67%) were returned for analysis. The results suggest that product quality partially mediated the relationship between technology transfer and competitiveness of SSABs. The results demonstrate further that the relationship between product quality and competitiveness was moderated by asset value such that at low levels of product quality, SSABs with larger asset values became more competitive than those with smaller asset values. However, as product quality increased, SSABs with smaller asset values became increasingly competitive until the competitive advantage of those with larger asset values was eliminated. SSABs in South Africa reported higher product quality and competitiveness than those in Zimbabwe. The relationship between the location in which the SSAB was situated and competitiveness was direct, and location did not moderate the relationship between technology transfer and competitiveness. The study illuminates the critical importance of product quality for SSABs, especially those with small asset values. It also demonstrates that while technology transfer may influence the competitiveness of SSABs directly, the influence of quality products cannot be underestimated. The study is one-of-a-kind that simultaneously considers explanatory and moderated effects of technology transfer-competitiveness nexus in SSABs, in the context of South Africa and Zimbabwe.
Keywords: 650; Technology transfer; Asset value; Competitiveness; Product quality; Small-scale agro-businesses